THE NATIONAL ECONOMY IS AFFECTED BY SUDDEN STOPS IN CAPITAL FLOWS - V. V. Arkhipova (Финансы: теория и практика)
The reasons for sharp changes in the direction of financial resource flows are a subject of research vital for any period of the global financial system history. The purpose of the study is to identify the main features of the financial phenomenon of a sudden stop in capital flows. To determine the theoretical parameters of the sudden stop in capital flows a review of the 1995-2015 literature was made. The likelihood of this event in the short and medium terms, in practice, is estimated based on the IMF, World Bank and the Bank of Russia data for the domestic economy for the period of 1994-2015. The study revealed three different approaches to the measurement and determination of a sudden stop in capital flows. In order to assess the significance of this financial problem for the national economy of Russia, a complex statistical analysis based on all the three approaches (the data of the financial account in the Russian balance of payments at one of the research stages was “cleared” from the reserves) was used.